2014
DOI: 10.1371/journal.pone.0090865
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and Analysis of Differential miRNAs in PK-15 Cells after Foot-and-Mouth Disease Virus Infection

Abstract: The alterations of MicroRNAs(miRNAs) in host cell after foot-and-mouth disease virus (FMDV) infection is still obscure. To increase our understanding of the pathogenesis of FMDV at the post-transcriptional regulation level, Solexa high-throu MicroRNAs (miRNAs) play an important role both in the post-transcriptional regulation of gene expression and host-virus interactions. Despite investigations of miRNA expression ghput sequencing and bioinformatic tools were used to identify differentially expressed miRNAs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…In viral disease research, miRNA profiling has become a topic of considerable interest as researchers search for cellular targets that can be exploited in order to combat infection. In the case of FMDV, the sole miRNA profiling study to date was an investigation of the differential expression of miRNAs in a porcine based cell line in response to infection with an isolate of FMDV serotype Asia1 [49]. The widespread utility of these findings is somewhat limited given that cell culture is not necessarily reflective of the molecular pathogenesis of the virus in an in vivo setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In viral disease research, miRNA profiling has become a topic of considerable interest as researchers search for cellular targets that can be exploited in order to combat infection. In the case of FMDV, the sole miRNA profiling study to date was an investigation of the differential expression of miRNAs in a porcine based cell line in response to infection with an isolate of FMDV serotype Asia1 [49]. The widespread utility of these findings is somewhat limited given that cell culture is not necessarily reflective of the molecular pathogenesis of the virus in an in vivo setting.…”
Section: Discussionmentioning
confidence: 99%
“…The previously reported miRNA profile of a porcine cell line infected with FMDV serotype Asia1 was obtained using high throughput sequencing [49], which represents the first time such a differential profiling experiment was performed for FMDV. The present study represents the first miRNA profiling experiment, albeit a limited small scale proof-of-concept study, using serum collected from uninfected and infected cattle.…”
Section: Discussionmentioning
confidence: 99%
“…These studies emphasize that miR-29b can modulate the pathogenesis of bovine viral diarrhea virus using different mechanisms. Along the same lines, PK-15 cells were used to screen for differentially expressed miRNAs during foot-and-mouth disease virus (FMDV) infection ( 166 ). The analysis revealed that 172 known miRNAs and 72 putative miRNAs were differentially expressed, the majority of which were downregulated.…”
Section: Micrornas In the Host Response To Viral Infections Of Veterimentioning
confidence: 99%
“…In the PK‐15 porcine kidney cell line, FMDV Asia 1 induced differential expression of 172 known, and 72 novel, miRNAs after 6 h, compared to non‐infected cells. Pathway annotation revealed that the miRNAs were abundant in cell death and immune response pathways (Zhang et al., ). In addition, another group working in China employed high‐throughput quantitative proteomics to analyse the global changes in protein expression in FMDV‐infected IBRS‐2 cells.…”
Section: Molecular Biologymentioning
confidence: 99%